Peran Al-Qur’an Raksasa Terhadap Peningkatan Wisata Religi di Kota Palembang - tunnaja, safina (Maliki Interdisciplinary Journal, 2024)
This article discusses the significant role of the Giant Qur’an in promoting religious tourism in Palembang City. The city has become a primary destination for tourists seeking profound spiritual experiences in Indonesia. The Giant Qur’an, a grand monument containing the Qur’anic text in extraordinary proportions, stands out as one of the city’s prominent icons. Through an in-depth analysis, this article explores several key aspects of the Giant Qur’an’s role in enhancing religious tourism in Palembang. Firstly, as a tourist attraction, this monument draws the attention of visitors who wish to experience the beauty of Islamic art and spirituality. Additionally, the Giant Qur’an also serves as a center for religious activities, such as study circles and recitations, making it a significant place for the local Muslim community and visitors from outside the city. Besides providing spiritual benefits, the presence of the Giant Qur’an also has a positive economic impact on Palembang. The surge in tourist visits has created new opportunities in the local tourism industry, including in accommodation, food, and local crafts sectors. Furthermore, this article discusses the important role of the Giant Qur’an as a means of education and understanding of Islamic teachings. Through various educational programs, visitors are encouraged to deepen their knowledge of the Qur’an and the religious values contained within. Therefore, this article concludes that the Giant Qur’an is not only a religious symbol but also a driving force in strengthening religious tourism in Palembang City. Its presence creates harmony between Islamic art, spirituality, and culture, making it one of the main destinations for religious tourists in Indonesia.